Nitric oxide and hydrogen sulfide modulate the NADPH-generating enzymatic system in higher plants - Corpas, Francisco J (Journal of experimental botany, 2021)
© The Author(s) 2020. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.